2022
DOI: 10.1007/s11356-022-20075-7
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the immunoboosting potential of macro and micronutrients in COVID support therapy

Abstract: The immune system protects human health from the effects of pathogenic organisms; however, its activity is affected when individuals become infected. These activities require a series of molecules, substrates, and energy sources that are derived from diets. The consumed nutrients from diets help to enhance the immunity of infected individuals as it relates to COVID-19 patients. This study aims to review and highlight requirement and role of macro- and micronutrients of COVID-19 patients in enhancing their immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 164 publications
0
9
0
Order By: Relevance
“…Syncytiotrophoblast cells regulate feto-maternal nutrient supply and gas exchange [ 55 ]. Therefore, a higher expression of placental ACE2 during pregnancy increases the risk of SARS-CoV2 infections during pregnancy and increases the risk of VT [ 39 , 56 , 105 , 106 ].…”
Section: Discussionmentioning
confidence: 99%
“…Syncytiotrophoblast cells regulate feto-maternal nutrient supply and gas exchange [ 55 ]. Therefore, a higher expression of placental ACE2 during pregnancy increases the risk of SARS-CoV2 infections during pregnancy and increases the risk of VT [ 39 , 56 , 105 , 106 ].…”
Section: Discussionmentioning
confidence: 99%
“…In its clinical perspective, IVN might be a pioneer drug in attenuating cardiotoxicity, mainly in patients with heart failure, arrhythmias, and malignancies treated by DXR. It has been shown that unlike β-blockers, IVN does not decrease ventricular force (Su et al 2020 ; Al-Kuraishy et al 2021b , 2022c , d ; Lawal et al 2021 ) and can also reduce COVID-19-induced cardiovascular complications due to its anti-inflammatory and antioxidant properties (Al-Kuraishy et al 2021c , 2022e ; Batiha et al 2021 , 2022 ). In addition, IVN facilitates a pleiotropic cardioprotective effect against isoproterenol-induced acute cardiac injury by increasing the ventricular fibrillation threshold (Simko et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the GDF15 was implicated in the pathogenesis of anemia by inhibiting the expression of hepcidin. However, hypoxia and anemia activate the expression and synthesis of GDF15 [ 42 , 43 ]. Lower hepcidin serum level is linked with COVID-19 severity and mortality [ 44 , 45 ].…”
Section: Growth Differentiation Factor 15 and Covid-19mentioning
confidence: 99%